Enhancing effect of vitexin on osteogenic activity of murine pre-osteoblastic MC3T3-E1 cells - Yuan, Xiaohan; Han, Haiyan; Luo, Zhaohui; Wang, Qiuxue; Tang, Peijia; Zhang, Zhihui; Fu, Yujie; Gu, Chengbo (Penerbit Universiti Kebangsaan Malaysia, 2020)
Vitexin (5,7,4-trihydroxyflavone-8-glucoside), a natural flavone present in a variety of plants, is well known for its rich pharmacological properties. However, its osteogenic activity remains unclear to date. The purpose of this study was to explore the effects of vitexin on osteogenic activity in murine pre-osteoblastic MC3T3-E1 cells using the MTT assay for cell proliferation, alkaline phosphatase (ALP) activity assay for cell differentiation, and Von Kossa staining for cell mineralization. Quantitative real-time PCR was used for the detection of osteocalcin (OCN) mRNA expression in cells. Furthermore, effects of vitexin on the differentiation and matrix mineralization of dexamethasone (DEX)- suppressed cells was also investigated. The results showed vitexin could significantly enhance cell proliferation in a low concentration range of 10-10-10-6 μg mL-1. ALP activity was significantly increased after the cells were treated with vitexin at 10-8 and 10-6 μg mL-1. The expression levels of the osteogenic OCN gene in cells treated with vitexin at 10-6, 10- 8, and 10-10 μg mL-1 were improved by 3.1-fold, 5.8-fold, and 4.2-fold over the control, respectively. Additionally, vitexin (10-8 μg mL-1) significantly alleviated the inhibitory effect of osteoblast differentiation and mineralization induced by DEX. Collectively, our findings suggest vitexin could enhance cell proliferation and osteogenic differentiation of MC3T3-E1 cells, as well as rescue the inhibitory effect of cell differentiation and matrix mineralization induced by DEX. Therefore, vitexin may be useful as a promising therapeutic agent for bone disease and plays an important role in the prevention of glucocorticoid-induced osteoporosis.